A149 TRP53 LOSS IN KRT15+ INTESTINAL STEM CELLS SEVERELY AFFECTS SECRETORY CELL FATE AND SELF-RENEWAL. (4th March 2021) - Dubey, A; Gonneaud, A; Giroux, V
Abstract: Background: Intestinal epithelium homeostasis is maintained by two main populations of stem cells: Lgr5+ and reserve stem cells. Under injury, cell plasticity has been observed in progenitor and differentiated cells. We recently reported that Krt15+ cells are present in small intestinal and colon epithelia, and harbor self-renewal, multipotent and regenerative capacities. As in Lgr5+ and reserve stem cells, hyperactivation of Wnt/b-catenin pathway in Krt15+ stem cells lead to tumor formation in the intestinal epithelium. While these intestinal stem cell populations can act as tumor-initiating cells in sporadic colon cancer, little is known about the cell-of-origin of colitis-associated colon cancer (CAC). TP53 alteration is reported as an early event in CAC. Therefore, we hypothesize that Trp53 loss specifically in Krt15+ stem cells will perturb the epithelial homeostasis and lead to tumor formation. Aims: Identify if Krt15+ cells may act as the cell-of-origin in colitis-associated colorectal cancer Methods: To induce Trp53 loss specifically in Krt15+ cells, we generated Krt15-CrePR1;Trp53 fl/fl ( Krt15 △Trp53 ) mice, induced Cre recombination by injecting RU486 (PR agonist) and euthanized the mice at different time points following recombination. Results Results: Twelve-month following Cre recombination, adenoma formation was observed in a small proportion of Krt15 △ Trp53 mice. Though, Trp53 loss in Krt15+ cells severely perturbed the small intestinal morphology in every mouse studied. Increased crypt length and villi width was observed in Krt15 △Trp53 vs control mice without any changes in cell proliferation. We also observed an increased number of Tuft cells and goblet cells in the villi of experimental mice. In the crypt, higher number of Paneth cells and aberrant presence of goblet cells were noted in Krt15 △Trp53 mice. Interestingly, we also observed crypt cells expressing goblet and Paneth cell markers and decreased Notch pathway activation suggesting dysregulation of secretory cell fate. Krt15 △Trp53 mice display higher number of fibroblasts in the villi and the submucosa, as well as thickening of the muscularis layer. Interestingly, similar observations (accumulation of secretory cells and fibrosis) have been reported in IBD patients, supporting the possible role of Krt15+ cells in CAC. Furthermore, crypts isolated from Krt15 △Trp53 mice rapidly die when seeded as organoids vs crypts from control mice, suggesting that the alterations observed in vivo in Paneth cells might interfere with the stem cell niche and therefore reduce self-renewal of Krt15+ cells. Conclusions: Trp53 loss specifically in Krt15+ cells impaired cell fate decision, induced secretory cell hyperplasia, affected self-renewal ability, and initiated adenoma formation supporting the possible role of Krt15+ cells in gut inflammation and cancer. Funding Agencies: Canada Research Chair, Cancer Research Society, CFI